Telemedicine for sustainable postoperative follow-up: a prospective pilot study evaluating the hybrid life-cycle assessment approach to carbon footprint analysis - Lathan, Ross; Hitchman, Louise; Walshaw, Josephine; Ravindhran, Bharadhwaj; Carradice, Daniel; Smith, George; Chetter, Ian; Yiasemidou, Marina (Frontiers in Surgery, 2024)
Introduction: Surgical site infections(SSI) are the most common healthcare-associated infection however access to healthcare services, lack of patient awareness of signs, and inadequate wound surveillance can limit timely diagnosis. Telemedicine for remote postoperative follow-up has been shown to improve healthcare efficiency without compromising clinical outcomes. Furthermore, telemedicine could reduce the carbon footprint of the National Health Service(NHS) through minimising patient travel, a significant contributor of CO2e. Adopting such innovative approaches, could aid in the Net-Zero target by 2045 target. This study aimed to analyse the feasibility and sustainability of telemedicine post-operative follow-up for diagnosis of SSI. Methods: Patients undergoing lower limb vascular procedures were reviewed remotely at 30 days post-operatively with a combined outcome measure (photographs and Bluebelle WHQ). A hybrid life-cycle assessment approach to carbon footprint analysis was used. The kgCO2e associated with remote methods was mapped prospectively. A simple outpatient clinic review, i.e. no further investigations or management required, was modelled for comparison. Department of Environment, Food and Rural Affairs (DEFRA) conversion factors plus healthcare specific sources were used to ascertain kgCO2e. Patient postcodes were applied to conversion factors based upon mode of travel to calculate kgCO2e for patient travel. Total and Median (IQR) carbon emissions saved were presented for both patients with and without SSI.Results: 31 patients (M:F 2.4, 66.6±11.7 years) were included. The median return distance for patient travel was 42.5km (7.2-58.7). Median reduction in emissions using remote followup was 41.2kgCO2e (24.5-80.3, p<0.001) per patient. The carbon offsetting value of remote follow-up is planting 1 tree for every 6.9 patients. Total carbon footprint of face-to-face follow-up was 2895.3kgCO2e, compared to 1301.3kgCO2e when using a remote first approach (P<0.001). Carbon emissions in participants without SSI was 700.2kgCO2e for clinic method and 28.8kgCO2e for remote follow-up.Discussion: This model shows that the hybrid life-cycle assessment approach is achievable and reproducible. Implementation of an asynchronous digital follow-up model is effective in substantially reducing the carbon footprint. Further work is needed to corroborate these findings on a larger scale, quantify the impact of telemedicine on patient's quality of life and incorporating kgCO2e into the cost analysis of potential SSI monitoring strategies.